Results of Teacher Supervision at SMP Xaverius 7 Palembang - Maria, Roswinda (PPSDP International Journal of Education, 2024)
The process of learning activities supervised by a supervisor or educational expert is known as educational supervision. Providing feedback to teachers, providing suggestions for improvement, and ensuring that the learning process is in accordance with predetermined standards are the main objectives of educational supervision. In addition, data collection, classroom observation, discussion, and the creation of innovative teaching strategies and corrective measures are also included in educational supervision. As a result, improving the quality of teaching and learning in educational institutions depends heavily on educational supervision. Curriculum development and classroom learning models are two areas where educational supervision has a great influence on educational progress. Qualitative research is the type of this study. This qualitative research explains how principals’ academic supervision affects teachers’ professional development and classroom teaching standards. At SMP Xaverius 7 Palembang, 109 people participated in the study: the principal, the curriculum teacher, five members of the supervision team, five teachers of Bahasa Indonesia, PAK, mathematics, and civics, and grade VIII students. Collaborate with schools to plan supervision implementation, monitor implementation, observe academic supervisor evaluations, investigate academic supervision activities, and analyze test results obtained during academic inspections.